Development of MgO concrete with enhanced hydration and carbonation mechanisms - Dung, N.T. (2018)
This study proposed the use of hydration agent (HA) and seeds to improve the hydration and carbonation of reactive magnesium cement (RMC)-based concrete formulations. Hydration of RMC was evaluated by isothermal calorimetry. Water absorption and compressive strength results were used to assess the mechanical performance of RMC-based concrete samples. Quantification of hydrate and carbonate phases was performed via XRD and TGA. Formation and morphology of carbonates were observed via BSE and SEM. In addition to increasing the utilization of RMC in the carbonation reaction and facilitating early strength development, the use of HA formed large carbonate phases, while the addition of seeds improved sample microstructures via the development of dense carbonate networks. The improvements in morphology, microstructure and carbonate content in samples involving the simultaneous use of HA and seeds resulted in 56% lower water absorption values and 46% higher 28-day compressive strengths (70MPa) in comparison to the control sample.